Gynaecological quandary-mucinous tumours of ovary - Bhardwaj, Bikram; Singh, Sanjay; Nandy, Souvik; Rani, Jaldi R.; Kumari, Anu; Tevatia, Akanksha; Gupta, Ankush; Mishra, Deepti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Mucinous ovarian cancer is a type of epithelial ovarian tumor. It might be considered a subtype of epithelial ovarian tumors but they present and behave significantly different from them. Appreciating these differences and specific evaluation can improve the management and prognosis in such cases. To highlight these difficulties and dilemmas, we present our experience of managing 5 such cases of mucinous tumours with varied presentation and the treatment protocols followed to get successful outcome in each case. First patient was a young patient with unilateral ovarian mass (8 cm size) with normal tumour markers who underwent laparoscopic cystectomy (in bag removal) for benign mucinous cystadenoma. Second patient who was a nulligravida with huge ovarian mass with normal tumour markers, fertility preservation surgery in the form of unilateral salpingo-oophrectomy with limited surgical staging was done in the background of borderline mucinous ovarian tumor. Third patient was perimenopausal lady having bilateral ovarian masses which turned out to be Borderline mucinous ovarian tumour on frozen and underwent complete surgical staging. Fourth patient was nulligravida who presented with a large size ovarian mass (20 cm) underwent staging laparotomy in view of mucinous carcinoma of ovary on frozen section. Fifth patient was an unusual presentation where a diagnosed case of carcinoma endometrium had simultaneous presence of bilateral ovarian masses giving impression of advanced Ca endometrium but to our utter surprise turned out to be a case of synchronous tumours (Ca endometrium + borderline mucinous tumours in both ovaries) on histopathology and immunohistochemistry (IHC) making it a case of synchronous tumours. The varied presentation of mucinous ovarian tumors needs to be understood in detail so that targeted treatments can be given for successful outcome.